Risk factors for criminal recidivism in older sexual offenders. - Fazel, S; Sjöstedt, G; Långström, N; Grann, M (2006)
Sexual offenders constitute a substantial proportion of the older male prison population. Recent research findings, with potential consequences for risk management, indicate that recidivism risk might be lower in older sexual offenders. We followed up all adult male sexual offenders released from prison in Sweden during 1993-1997 (N=1,303) for criminal reconviction for an average of 8.9 years. We studied rates of repeat offending (sexual and any violent) by four age bands (<25, 25-39, 40-54, and 55+years), and examined whether risk factors for recidivism remained stable across age groups. Results showed that recidivism rates decreased significantly in older age bands. In addition, the effect of certain risk factors varied by age band. These findings on recidivism rates in older sexual offenders concur with studies from the United Kingdom, United States, and Canada and may suggest some generalizability in Western settings. Further research is needed to address underlying mechanisms.